Activation of the RpoN-RpoS regulatory pathway during the enzootic life cycle of Borrelia burgdorferi - Ouyang, Zhiming (BioMed Central, 2012)
BACKGROUND: The maintenance of Borrelia burgdorferi in its complex tick-mammalian enzootic life cycle is dependent on the organism's adaptation to its diverse niches. To this end, the RpoN-RpoS regulatory pathway in B. burgdorferi plays a central role in microbial survival and Lyme disease pathogenesis by up- or down-regulating the expression of a number of virulence-associated outer membrane lipoproteins in response to key environmental stimuli. Whereas a number of studies have reported on the expression of RpoS and its target genes, a more comprehensive understanding of when activation of the RpoN-RpoS pathway occurs, and when induction of the pathway is most relevant to specific stage(s) in the life cycle of B. burgdorferi, has been lacking. RESULTS: Herein, we examined the expression of rpoS and key lipoprotein genes regulated by RpoS, including ospC, ospA, and dbpA, throughout the entire tick-mammal infectious cycle of B. burgdorferi. Our data revealed that transcription of rpoS, ospC, and dbpA is highly induced in nymphal ticks when taking a blood meal. The RpoN-RpoS pathway remains active during the mammalian infection phase, as indicated by the sustained transcription of rpoS and dbpA in B. burgdorferi within mouse tissues following borrelial dissemination. However, dbpA transcription levels in fed larvae and intermolt larvae suggested that an additional layer of control likely is involved in the expression of the dbpBA operon. Our results also provide further evidence for the downregulation of ospA expression during mammalian infection, and the repression of ospC at later phases of mammalian infection by B. burgdorferi. CONCLUSION: Our study demonstrates that the RpoN-RpoS regulatory pathway is initially activated during the tick transmission of B. burgdorferi to its mammalian host, and is sustained during mammalian infection.